Hubungan Motivasi Belajar dengan Prokrastinasi Akademika pada Mahasiswa Manajemen Informasi Kesehatan - Nurniat O Gulo; Desnata E Zega (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Procrastination is related to fear of failure, dislike of assigned tasks, resistance and resistance to control, dependency and difficulty in making decisions. Academic procrastination is a type of delay that is carried out on types of formal tasks related to academic tasks such as lecture assignments from lecturers. Learning motivation is an effort that is realized by the teacher to create a desire in students who support activities towards learning goals. This study aims to determine the relationship between learning motivation and academic procrastination in health information management students. The type of research used in this research is cross sectional. Data retrieval through questionnaires distributed online using google form. The population in this study amounted to 47 people on 28 June-21 July 2022, the sampling technique was carried out by total sampling. The location of the research was carried out in the STIKes Santa Elisabeth dormitory, Medan. Research results Based on the Spearman Rank test (Rho) obtained p-value = 0.431, so it can be concluded that Ha is rejected so that Ho is accepted, meaning there is no relationship between student learning motivation and academic procrastination on Health Information Management students at STIKes Santa Elisabeth Medan.